Prediction of objectively measured physical activity and sedentariness among blue-collar workers using survey questionnaires - Gupta, Nidhi; Heiden, Marina; Mathiassen, Svend Erik; Holtermann, Andreas (Scandinavian Journal of Work, Environment & Health, 2016)
' ' OBJECTIVES ': 'We aimed at developing and evaluating statistical models predicting objectively measured occupational time spent sedentary or in physical activity from self-reported information available in large epidemiological studies and surveys. ' ' METHODS ': 'Two-hundred-and-fourteen blue-collar workers responded to a questionnaire containing information about personal and work related variables, available in most large epidemiological studies and surveys. Workers also wore accelerometers for 1–4 days measuring time spent sedentary and in physical activity, defined as non-sedentary time. Least-squares linear regression models were developed, predicting objectively measured exposures from selected predictors in the questionnaire. ' ' RESULTS ': 'A full prediction model based on age, gender, body mass index, job group, self-reported occupational physical activity (OPA), and self-reported occupational sedentary time (OST) explained 63% (R2 adjusted) of the variance of both objectively measured time spent sedentary and in physical activity since these two exposures were complementary. Single-predictor models based only on self-reported information about either OPA or OST explained 21% and 38%, respectively, of the variance of the objectively measured exposures. Internal validation using bootstrapping suggested that the full and single-predictor models would show almost the same performance in new datasets as in that used for modelling. ' ' CONCLUSIONS ': 'Both full and single-predictor models based on self-reported information typically available in most large epidemiological studies and surveys were able to predict objectively measured occupational time spent sedentary or in physical activity, with explained variances ranging from 21–63%.
Keywords: accelerometry; actigraph; blue-collar worker; objective measure; physical activity; prediction; prediction model; questionnaire; sedentariness; sedentary time